Being Israeli : the dynamics of multiple citizenship - Shafir, Gershon (Cambridge Middle East studies, 2002)
The authors speculate on the relationship between identity and citizenship in Israeli society and explore the differential rights accorded different social strata. They conclude that, despite ongoing tensions, globalization and economic liberalization have transformed Israel from a frontier society to one more oriented towards peace and private profit.